An Integrated Method for Building Kampung Zakat Program in Sidomulyo, Bengkulu Province (UIN Sunan Kudus, 2023)
This study is aimed at determining the advantages and disadvantages as well as future improvements to maximize the objectives of Kampung Zakat program. The qualitative method was adopted involving 35 informants and the data collection methods include observation, interviews, FGD, and open questionnaires. Data were analyzed using the stages in the analysis qualitative technique of Miles and Huberman. The results showed that the implementation of community development based on Kampung Zakat was not carried out according to plan. Therefore, Kampung Zakat development model must pay attention to the needs of the community, should not be limited to a single activity, and relies solely on the synergy between the community, government, BAZNAS, and stakeholders. The result implies that building a community is not an easy task and cannot be accomplished in a short time. Kampung Zakat program, whose primary objective is to build a community based on the potential of zakat, infak, alms, and waqf, has not been able to materialize. At least some parties contribute to the failure of this program, and its continuation requires synergy from various stakeholders or partners of Kampung Zakat. The presence of a leader or person with initiative is also very important. The significance of this research is as an evaluative resource for the Zakat Village Program's stakeholder program's enhancement programs.